2014
DOI: 10.1093/gerona/glu006
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Physical Exercise Delays Age-Associated Skeletal Muscle Decline

Abstract: Aging is usually accompanied by a significant reduction in muscle mass and force. To determine the relative contribution of inactivity and aging per se to this decay, we compared muscle function and structure in (a) male participants belonging to a group of well-trained seniors (average of 70 years) who exercised regularly in their previous 30 years and (b) age-matched healthy sedentary seniors with (c) active young men (average of 27 years). The results collected show that relative to their sedentary cohorts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
220
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(237 citation statements)
references
References 58 publications
(56 reference statements)
7
220
3
2
Order By: Relevance
“…Individual physical activity history and aerobic and resistance training interventions, which are the major focus of this review, seem to be associated with the reversibility of sarcopenia. Indeed, recent findings suggest that regular skeletal muscle contraction, such as a resistance training program of at least 12 weeks [68] or a combination of ET and RT activities [69] counteract the detrimental effects of a sedentary lifestyle, as well as the regular use of neuromuscular electrical stimulator [70]. Indeed, they represent a good intervention to attenuate and slightly reverse the decline of skeletal myofiber size, strength, and power associated with the ultrastructural disorders observed during aging.…”
Section: Aging Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Individual physical activity history and aerobic and resistance training interventions, which are the major focus of this review, seem to be associated with the reversibility of sarcopenia. Indeed, recent findings suggest that regular skeletal muscle contraction, such as a resistance training program of at least 12 weeks [68] or a combination of ET and RT activities [69] counteract the detrimental effects of a sedentary lifestyle, as well as the regular use of neuromuscular electrical stimulator [70]. Indeed, they represent a good intervention to attenuate and slightly reverse the decline of skeletal myofiber size, strength, and power associated with the ultrastructural disorders observed during aging.…”
Section: Aging Skeletal Musclementioning
confidence: 99%
“…Moreover, a greater proportion of mitochondria in the elderly are depolarized or nonfunctional, which may be indicative of defects in mitochondrial turnover [74]. The density of mitochondria in skeletal muscle also drops considerably with aging [75], as shown, for example, by means of electron microscopy in the vastus lateralis muscle of people over 60 years of age when compared to their younger counterparts [60,76]. Boncompagni et al, with an elegant study, observed a decrease in the frequency of CRUs at sarcomere's I-A band transition and tethered mitochondria [61] with aging, as mitochondria are reduced in terms of content, function, and turnover in both subsarcolemmal and intermyofibrillar pools [77].…”
Section: Aged-related Changes In Skeletal Muscle Mitochondriamentioning
confidence: 99%
“…QMC-CT is a highly sensitive quantitative imaging analysis recently developed by the group of Prof. Paolo Gargiulo to monitor skeletal muscle and perform follow-up examinations of muscle affected by wasting conditions [116][117][118][119][120]. Through the successful EU Program: RISE [Use of electrical stimulation to restore standing in paraplegics with longterm denervated degenerated muscles (QLG5-CT-2001-02191), and INTERREG III and IV: European Regional Development Fund, project Mobilität im Alter, MOBIL, N_00033)], we have demonstrated, mainly through the use of QMC-CT, that h-bFES therapy improves the muscle quality of mobility impaired persons [9] and of healthy seniors [114].…”
Section: Quantitative Computed Tomography and Image Analysis For Advamentioning
confidence: 88%
“…It is known that skeletal muscle deteriorates in response to nerve or muscle damage, prolonged bed rest, diseases such as sepsis, and with normal aging [114]. The follow-up of muscle atrophy/degeneration in neuro-muscularly traumatized people is difficult because of the lack of adequate imaging analyses and also the practical and ethical constraints on harvesting the muscle biopsies necessary to monitor the efficacy of the therapy/rehabilitation strategies.…”
Section: Quantitative Computed Tomography and Image Analysis For Advamentioning
confidence: 99%
“…To support the project, denervated muscle fibrillation analyses are revisited in the article of Pond A, Marcante A, Zanato R, Martino L, Stramare R, Vindigni V, Zampieri S, Kern H, Masiero S, Piccione F "History, mechanisms and clinical value of fibrillation analyses in muscle denervation and reinnervation by Single Fiber Electromiography and Dynamic Echomyography". 20 Further, in collaboration with his international partners, Dr. Kern is extending the benefits of h-b FES to those subjects, which for different reasons suffer the consequences of muscle weakness, from the mild but unrelenting process of aging, [21][22][23][24] to the devastating fast progression of muscle cachexia in cancer patients. 25,26 The present 25 (4) …”
mentioning
confidence: 99%